2017
DOI: 10.1108/lhtn-02-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Do literature festivals promote reading and public libraries? A survey

Abstract: Purpose The purpose of this paper is to study the relationship between public libraries, literature festivals (litfests) and reading habits in Chennai and Bangalore to understand publishing, reading and the role of public libraries to improve reading and learning among public. Design/methodology/approach A field visit to select book fairs and litfests in Chennai and Bangalore was undertaken in 2015 and 2016 to collect data. A predesigned questionnaire was used for data collection at the festivals to establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Contradicting Kruger and Saayman (2018a, b) who identified the sharing of experiences as a behavioural intention respectively at a music festival and lifestyle and décor exhibition, this research but stresses the finding by Kruger and Saayman (2018a) that purchasing behaviour is an important behavioural intention. This factor is further supported by Kulkarni et al (2017) who revealed that attending literary festivals influences book purchases. LASP should, therefore, be enhanced by providing visitors with opportunities to purchase literary arts not only during the festival but also after attending it.…”
Section: Findings and Implicationsmentioning
confidence: 64%
See 1 more Smart Citation
“…Contradicting Kruger and Saayman (2018a, b) who identified the sharing of experiences as a behavioural intention respectively at a music festival and lifestyle and décor exhibition, this research but stresses the finding by Kruger and Saayman (2018a) that purchasing behaviour is an important behavioural intention. This factor is further supported by Kulkarni et al (2017) who revealed that attending literary festivals influences book purchases. LASP should, therefore, be enhanced by providing visitors with opportunities to purchase literary arts not only during the festival but also after attending it.…”
Section: Findings and Implicationsmentioning
confidence: 64%
“…Along with the qualities above, literary arts festivals introduce readers to new authors and often profile emerging writers at a critical stage in their career; however, they also build community between writers and other members of the literary community (Benaway, 2016). Kulkarni et al (2017) in their research, revealed that attending literary festivals can influence and improve reading habits and increase book purchases, while Elbeshausen (2015) focussed on the importance of these types of festivals to enhance cultural entrepreneurship. The literature festival audience is described as high-brow, educated, middle class, with women being overrepresented in fiction events and men in non-fiction.…”
Section: Introductionmentioning
confidence: 99%
“…Public library infrastructure in India remains neglected and underfunded and is often the lowest of priorities for everyone -from government to corporations to civil society. "Eminent historian and a resident of Bangalore, Ramachandra Guha, had criticized big IT companies for not opening libraries in the city" (Kulkarni et al, 2017). "Speaking at the inaugural of Bangalore Book Festival 2015, Guha had said that he feels abused when Bangalore is termed as the intellectual capital.…”
Section: Current Public Library Situation In Indiamentioning
confidence: 99%
“…The results of various studies reveal that the literature reading habits of the students vary between genders and regions. Kulkarni, Dhanamjaya and Balaji (2017) found that the majority of the respondents agreed (46.1%) and strongly agreed (33%) that visiting literature festivals would influence or improve reading habits.…”
mentioning
confidence: 91%